Comprehensive experimental investigations and theoretical predictions on the physical properties of natural rubber composites. Issue 47 (5th October 2022) - Abhisha, Vakkoottil Sivadasan; Sisanth, Krishanagegham Sidharathan; Parameswaranpillai, Jyotishkumar; Pulikkalparambil, Harikrishnan; Siengchin, Suchart; Thomas, Sabu; Stephen, Ranimol
Abstract: Conducting elastomers are highly desirable in the present world because of their major applications in the electronic industry. Conductive carbon black (CCB) is a conventional reinforcing filler commonly used in elastomers to modify the mechanical as well as electrical properties. The present study focuses on the experimental and theoretical computation of filler reinforcement, dielectric, mechanical, dynamic mechanical, and surface morphology of natural rubber (NR)/CCB composites. Two step processing method is adopted to attain homogeneous dispersion of filler in the matrix: preparation of NR/CCB masterbatch through melt mixing using internal mixer followed by compounding in a two‐ roll mill. Improved DC conductivity in the order of 10 −6 was obtained at higher filler loading indicating the formation of a continuous conductive network in the matrix. Percolation threshold was computed using Power law equation and obtained a value of 0.154 vol%. Theoretical predictions of mechanical modulus and tensile strength were done using rule of mixtures, Einstein, Guth and Kerner models and Nicolais‐Narkis and Kuneri‐Geil models respectively. A remarkable change in tensile strength is observed for NR as a function of the weight percentage of CCB; it is increased to 26.3 ± 0.9 MPa at 20 phr CCB from 17.1 ± 0.9 MPa for NR. Abstract :